Religious and political discourse in Argentina: The case of reconciliation - Bonnin, Juan Eduardo (2009)
This article analyzes the nominalization 'reconciliation' as a grammar metaphor that allows for the understanding of the historical relationships between religious and political discourse in Argentina. In order to do this, we will analyze the case of the publication of the Final Document of the Military Junta on the Fight against Terrorism and Subversion, in 1983, and its subsequent interpretations made by political and religious actors in terms of its adequacy or inadequacy to the Catholic proposal of reconciliation, which would later become a legal argument in the penal trials sustained against human rights violators. We will observe two relevant features: (a) a struggle about the experiential meaning concealed by the nominalization that legitimates or, on the contrary, de-legitimates the repressive action of the Military Junta; (b) an implicit consensus that attributes to Catholic discourse the power to dictate the rules of political life, which has severely restrained the autonomy of political democratic actors.